Simulation Analysis of an Electric Locomotive with a Hydraulic Wheelset Guidance System for Improved Performance in Curved Tracks - Jan Kalivoda (Machines)
A reduction of forces acting between the railway track and the vehicle is one of the key issues in the design of modern rolling stock. Because the capabilities of reducing wheel–rail contact forces in track curves by conventional methods are encountered at their limits, innovative approaches in the design of vehicle suspension and wheelset guidance occur. Among them, an active wheelset steering appears to be very promising. However, an active wheelset steering system is rather complicated and expensive and raises many safety issues. Therefore, a passive hydraulic system that links longitudinal motions of axle boxes is proposed. The system is relatively simple and, compared to the active wheelset steering, does not need any energy supply or sensor system for the detection of a track shape. Two arrangements of the hydraulic system had been proposed and implemented in a simulation model. The simulation model is based on a cosimulation of two separate models, a multibody model of an electric locomotive, and a model of the hydraulic system. The goal of this study is to evaluate the contribution of the hydraulic system to the natural radial alignment of wheelsets in curves and thus to reduce the wear of wheels and to determine the parameters of the hydraulic system to maximize the wear reduction benefits while minimizing a decrease in critical speed. Simulations of a vehicle running in various scenarios, including a run in a real track section of a length of 20 km, have been performed. As a criterion for the wear of wheels and rails, a T-gamma wear number was used, from which a sum of frictional work in wheel–rail contacts was calculated. The results of the simulations and the comparison of hydraulic axle box connection systems and a standard locomotive are presented and discussed in the paper. The results obtained confirmed a significant potential benefit of the proposed hydraulic system in reducing wheel wear on curved tracks.